The Three Brides - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Three Brides" by Charlotte M. Yonge is a novel written in the mid-19th century. The story revolves around the lives and marriages of three brothers and their respective brides, focusing on the dynamics within the family and the relationships that develop as they navigate society's expectations and personal challenges. Central to the narrative is Mrs. Charnock Poynsett, the mother of the brothers, who balances her deep affection for her sons with the changes brought by their marriages. The opening of the story introduces several key characters and sets the stage for the arrival of the brides. Mrs. Poynsett is preparing for the homecoming of her sons and their newlywed wives, demonstrating both excitement and concern about the transitions taking place within their family. The chapter captures the intricate family dynamics, with playful banter among the sons, the mother$1 (Bs nostalgia, and hints of the brides' personalities as they come into the household. As the characters interact, the reader gets a sense of their backgrounds and the societal conventions of the time, as well as the brewing tension and excitement of these new familial additions. (This is an automatically generated summary.)s
Release date is 2004-06-01
Transcribed by David Price
Keywords: England -- Social life and customs -- 19th century -- Fiction; Marriage -- Fiction